Equilibrium Tuition, Applications, Admissions, and Enrollment in the College Market - Fu, Chao (Journal of Political Economy, 2014)
I develop and estimate a structural equilibrium model of the college market. Students, having heterogeneous abilities and preferences, make application decisions subject to uncertainty and application costs. Colleges, observing noisy measures of student ability, choose tuition and admissions policies to compete for better students. Tuition, applications, admissions, and enrollment are joint equilibrium outcomes. I estimate the model using the NLSY97 via a three-step procedure to deal with potential multiple equilibria. I use the model to examine the extent to which college enrollment can be increased by expanding college supply and to assess the importance of various measures of student ability.